Sensitivity and Specificity of On-Field Visible Signs of Concussion in the National Football League. Issue 3 (15th April 2020) - Elbin, Robert J; Zuckerman, Scott L; Sills, Allen K; Crandall, Jeff R; Lessley, David J; Solomon, Gary S
Abstract: BACKGROUND: On-field visible signs (VS) are used to help identify sport-related concussion (SRC) in the National Football League (NFL). However, the predictive utility of a VS checklist for SRC is unknown. OBJECTIVE: To report the frequency, sensitivity, specificity, and predictive value of VS in a cohort of NFL athletes. METHODS: On-field VS ratings from 2 experts who independently reviewed video footage of a cohort of 251 injury plays that resulted in an SRC diagnosis (n = 211) and no diagnosis (n = 40) from the 2017 NFL season were examined. The frequency, sensitivity, specificity, and a receiver operating characteristic (ROC) curve with area under the curve (AUC) were calculated for each VS. RESULTS: Slow to get up (65.9%) and motor incoordination (28.4%) were the most frequent VS in concussed athletes, and slow to get up (60.0%) was the most common VS among nonconcussed athletes. The most sensitive VS was slow to get up (66%); the most specific signs in concussed NFL athletes were blank/vacant look and impact seizure (both 100%). Approximately 26% of concussed NFL players did not exhibit a VS, and the overall sensitivity and specificity for the VS checklist to detect SRC were 73% and 65%, respectively. The VS checklist demonstrated "poor" ability to discriminate between SRC and non-SRC groups (AUC = 0.66). CONCLUSION: In the NFL, the diagnosis of concussion cannot be made from on-field VS alone. The VS checklist is one part of the comprehensive sideline/acute evaluation of concussion, and the diagnosis remains a multimodal clinical decision. Graphical Abstract: